Tinjauan Yuridis Terhadap Upaya Hukum Kasasi Jaksa Penuntut Umum Atas Putusan Bebas Pada Kasus Baiq Nuril Berdasarkan Pasal 244 Kitab Undang-Undang Hukum Acara Pidana - Muhammad Zainal; Kholidazia El. HF. (JUSTNESS - Jurnal Hukun dan Agama, 2021)
All citizens are equal before the law and are obliged to uphold the law and the government with no exceptions", the quote is the content of Article 27 paragraph 1 of the 1945 Constitution. The constitution is the highest law above other laws. This article is a mandate that we must obey as citizens, so that whoever and whatever our position is, of course we must obey a rule of law without any exceptions, in order to create a sense of security and peace, because the law has a rule and principle which is the main foundation. of the law itself, namely providing a sense of justice, benefits and certainty. In the law enforcement process carried out by court agencies, the final point is a decision taken by the panel of judges, and every decision taken will certainly lead to a polemic, one party considers the decision fair and on the other side considers the decision unfair, so that the principle of Certainty of the law itself is sometimes biased. Although in essence the law functions to ensure a sense of security, order and peace in society, behind that it is not uncommon for the law to sometimes create unrest in the community, because after all the law cannot be separated from society as a legal subject, and vice versa, society cannot be separated from the law, as stated in the statement. Cicero "Ubi Societi Ibi Ius, Ibi Ius Ubi Society" where there is society there is law, where there is law there is society. This research is normative but raises a legal case that is phenomenal and viral on social media and becomes a polemic in the midst of society, as if something went wrong in its application, namely the acquittal of a defendant but was appealed by the Public Prosecutor so that it seemed contradictory. with actual legal norms and there is no legal certainty and does not provide a portion of justice as the function of the law itself, in this context the author is interested in studying it in this study so that the polemics that arise can be studied in terms of the existing rules. Because this case has attracted the attention of many people who think that the law is not in place, "the strong are immune to the law while the weak are oppressed, the law is sharp downwards but blunt upwards" statements such as. That's what often appears when the weak do not get justice. Because of the polemics that arose in this case, the author is interested in examining it in an application of the articles in the Criminal Procedure Code as a basis for providing an explanation of the cases raised in this study, as the provisions of the law are juridical normative empirical. Keyword: Yiridis Review, Cassation Legal Effort, Free Decision, Article 244 of the Criminal Code